Intermolecular photocatalyzed heck-like coupling of unactivated alkyl bromides by a dinuclear gold complex - Xie, Jin; Li, Jian; Claus, Vanessa; Rudolph, Matthias; Hashmi, A. Stephen K. (Chemistry - a European journal, 2016)
A practical protocol for a photocatalyzed alkyl-Heck-like reaction of unactivated alkyl bromides and different alkenes promoted by dinuclear gold photoredox catalysis in the presence of an inorganic base is reported. Primary, secondary, and tertiary unactivated alkyl bromides with β-hydrogen can be applied. Esters, aldehydes, ketones, nitriles, alcohols, heterocycles, alkynes, alkenes, ethers, and halogen moieties are all well tolerated. In addition to 1,1-diarylalkenes, silylenolethers and enamides can also be applied, which further increases the synthetic potential of the reaction. The mild reaction conditions, broad substrate scope, and an excellent functional-group tolerance deliver an ideal tool for synthetic chemists that can even be used for challenging late-stage modifications of complex natural products.